TRPC1 contributes to the Ca(2+) -dependent regulation of adenylate cyclases - Willoughby, Debbie (Biochem J, 2014)
SOCE (store-operated Ca(2+) entry) is mediated via specific plasma membrane channels in response to ER (endoplasmic reticulum) Ca(2+) store depletion. This route of Ca(2+) entry is central to the dynamic interplay between Ca(2+) and cAMP signalling in regulating the activity of Ca(2+) -sensitive adenylate cyclase isoforms (AC1, AC5, AC6 and AC8). Two proteins have been identified as key components of SOCE: STIM1 (stromal interaction molecule 1), which senses ER Ca(2+) store content and translocates to the plasma membrane upon store depletion, where it then activates Orai1, the pore-forming component of the CRAC (Ca(2+) release-activated Ca(2+)) channel. Previous studies reported that co-expression of STIM1 and Orai1 in HEK-293 (human embryonic kidney 293) cells enhances Ca(2+) -stimulated AC8 activity and that AC8 and Orai1 directly interact to enhance this regulation. Nonetheless, the additional involvement of TRPC (transient receptor potential canonical) channels in SOCE has also been proposed. In the present study, we evaluate the contribution of TRPC1 to SOCE-mediated regulation of Ca(2+) -sensitive ACs in HEK-293 cells stably expressing AC8 (HEK-AC8) and HSG (human submandibular gland) cells expressing an endogenous Ca(2+) -inhibited AC6. We demonstrate a role for TRPC1 as an integral component of SOCE, alongside STIM1 and Orai1, in regulating Ca(2+) fluxes within AC microdomains and influencing cAMP production.